Biotic potential, fertility and life table ofSpodoptera albula (Walker) (Lepidoptera: Noctuidae), under controlled conditions - MONTEZANO,DÉBORA G. (2014)
This study aimed to evaluate the biotic potential, life table parameters and fertility of Spodoptera albula (Walker, 1857) under controlled conditions (25 ± 1°C, 70 ± 10% RH and 14 hour photo phase). The longevity, pre, post and oviposition periods, fecundity and fertility of 13 couples were evaluated. The longevity of females (13.500 days) was significantly higher than those of males (11.154 days). The mean durations of the pre, post and oviposition periods were 2.615, 1.769 and 9.385 days, respectively. The mean fecundity was 1.417.69 eggs and mean fertility was 1.340.401 larvae, per female. On average, females copulated 1, 231 times. A strong positive correlation was observed between the number of copulations and fecundity (r = 0.847, p <0.001), as well as a strong negative correlation between the number of copulations and the duration of the pre-oviposition period (r = -0.762, p = 0.002), and longevity (r = -0.788, p = 0.001). The biotic potential of S. albula was estimated at 8.768 x 1022 individuals / female / year. The net reproductive rate (Ro) was 353,904 times per generation and the mean generation time (T) was 37.187 days. The intrinsic rate of increase (rm) was 1,105, with a finite rate of increase (λ) of 3,019.